Key issues in addressing the clinical and humanistic burden of short bowel syndrome in the US. (May 2013) - Hofstetter, Steven; Stern, Lee; Willet, Jacob
Abstract Background: The purpose of this analysis was to provide a concise report of the literature on the burden of intestinal failure associated with short bowel syndrome (SBS–IF) in adults, focused on clinical and humanistic issues important to clinicians and payers. Scope: A literature search was performed using the National Library of Medicine PubMed database (http://www.ncbi.nlm.nih.gov/pubmed) with the search term 'short bowel syndrome' limited to adult populations and English-language reports published from January 1, 1965, to January 18, 2013. Citations were assessed for relevance and excluded articles focused on single case studies, colon fermentation, absorption of medications with PN/IV, surgical technique, mesenteric artery complications/surgery, and transplantation focus. Additional hand searches were performed using the terms 'short bowel syndrome' AND 'cost', and 'home parenteral nutrition' AND 'cost', along with the exclusion criteria described above. Findings: Despite advances in management in recent decades, SBS–IF continues to carry a high burden of morbidity and mortality. In the absence of sufficient intestinal adaptation following resection, many patients remain dependent on long-term parenteral nutrition and/or intravenous fluids (PN/IV). Although potentially life saving, PN/IV is costly, invasive, and associated with numerous complications and deleterious effects on health and quality of life. Surgical interventions, especially intestinal transplantation, are costly and are associated with substantial morbidity and high mortality. New therapies, which show promise in promoting intestinal rehabilitation and reducing dependence on PN/IV therapy, are the subject of active research. Conclusions: Overall, the available literature suggests that although SBS–IF affects a relatively small population, the clinical and humanistic burden is significant, and there is an unmet need for effective therapeutic options that target the underlying problem of inadequate absorptive capacity of the remaining intestine. Consequently, many patients with SBS–IF remain dependent on long-term PN/IV support, adding to the burden imposed by the underlying disorder.